Succession Planning As A Tool Of Employee Retention And Reduction In Recruitment Cost - Sudhanshu Dwivedi; Dr. Sneh P. Daniel (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2021)
With the aim to measure the practice of Succession Planning as a tool for employee retention and reduction in recruitment costs. Succession planning is a hard process for an organization that ensures that the employees are recruited and more developed to fit in each required key role within the company. By succession planning process, organizations recruit superior employees, train and develop their knowledge & abilities, and prepare them for advancement to face more challenging roles. Succession planning ensures that employees are constantly developed as per the needed role. As the organization expands its branches, it provides promotional opportunities, and increases sales, during this succession planning guarantees to have employees, ready and waiting to face new challenges. And if the employees are empowered by continuous learning and development processes and can avail better career opportunities in the organization a concern can retain its talent for longer tenure with low recruitment costs.